Public Education and Social Citizenship - Potentials and Pitfalls - Ray , Paroma (South Asian Journal of Social Sciences and Humanities, 2020)
In this paper I aim to explore the ideological and practical connections between citizenship and public  education. Drawing from Marshall’s social citizenship I will attempt to explore the strands of ideas  that facilitate or restrict the growth of social citizenship. The idea of global cosmopolitan citizenship  and Deep citizenship will be of special interest to me and I shall attempt to locate the ethics behind  them and how it ties up with public education. Questions of justice and equality and rights will be the  ethical considerations that would form an undercurrent to my discussion on citizenship and education.  Walzer, Agamben and Arendt’s ideas will be important in order to understand these dimensions. I will  also attempt to briefly trace the evolution of the concept of mass education and public education and  look at both nationalizing as well as globalizing tendencies in its history. While I will be looking at  the educational policies of India, I shall focus on only those aspects of education in India that fit the  general frame of the debates happening globally. Lastly, I will focus on the specific question of  movement of both citizens and non-citizens and its relationship with public education. Given that  education takes place over a decade of someone’s life informal movement has significant impact on  the breaks and continuity in one’s education and in one’s perception of oneself as a member of a  productive community that puts a premium value on education and educational qualifications while  allowing for the exploitation of those without an education.
Keywords: Public education; citizenship; social production; migration; mobility